General assisted living system architecture model - Trajkovik, Vladimir; Vlahu-Gjorgievska, Elena; Koceski, Sasho; Kulev, Igor (Springer International Publishing, 2015)
Novel information and communication technologies create possibilities to change the future of health care and support. Ambient Assisted Living (AAL) is seen as a promising alternative to the current care models so a number of researchers have developed AAL systems with promising results. The main goal of AAL solutions is to apply ambient intelligence technologies to enable people with specific needs to continue to live in their preferred environments. In this paper we are presenting a general architecture of system for assisted living that supports most of the use cases for such system.
Keywords: assisted living, wearable sensors, environmental sensors, social networks